Fluid Dynamics in a Thrust Fault Inferred from Petrology and Geochemistry of Calcite Veins: An Example from the Southern Pyrenees. (25th September 2020) - Muñoz-López, Daniel; Cruset, David; Cantarero, Irene; Benedicto, Antonio; John, Cédric M.; Travé, Anna
Abstract : Petrographic and geochemical analyses ( δ 18 O, δ 13 C, 87 Sr/ 86 Sr, clumped isotopes, and elemental composition) coupled with field structural data of synkinematic calcite veins, fault rocks, and host rocks are used to reconstruct the episodic evolution of an outstanding exposed thrust zone in the Southern Pyrenees and to evaluate the fault behavior as a conduit or barrier to fluid migration. The selected thrust displaces the steeply dipping southern limb of the Sant Corneli-Bóixols anticline, juxtaposing a Cenomanian-Turonian carbonate unit against a Coniacian carbonate sequence. Successive deformation events are recorded by distinct fracture systems and related calcite veins, highlighting (i) an episodic evolution of the thrust zone, resulting from an upward migration of the fault tip (process zone development) before growth of the fault (thrust slip plane propagation), and (ii) compartmentalization of the thrust fault zone, leading to different structural and fluid flow histories in the footwall and hanging wall. Fractures within the footwall comprise three systematically oriented fracture sets (F1, F2, and F3), each sealed by a separate generation calcite cement, and a randomly oriented fracture system (mosaic to chaotic breccia), cemented by the same cements as fracture sets F1 and F2. The formation of fractures F1 and F2 and the mosaic to chaotic breccia is consistent with dilatant fracturing within the process zone (around the fault tip) during initial fault growth, whereas the formation of the latest fracture system points to hybrid shear-dilational failure during propagation of the fault. The continuous formation of different fracture systems and related calcite cementation phases evidences that the structural permeability in the footwall was transient and that the fluid pathways and regime evolved due to successive events of fracture opening and calcite cementation. Clumped isotopes evidence a progressive increase in precipitation temperatures from around 50°C to 117°C approximately, interpreted as burial increase linked to thrust sheet emplacement. During this period, the source of fluid changed from meteoric fluids to evolved meteoric fluids due to the water-rock interaction at increasing depths and temperatures. Contrary to the footwall, within the hanging wall, only randomly oriented fractures are recognized and the resulting crackle proto-breccia is sealed by a later and different calcite cement, which is also observed in the main fault plane and in the fault core. This cement precipitated from formation fluids, at around 95°C, that circulated along the fault core and in the hanging wall block, again supporting the interpretation of compartmentalization of the thrust structure. The integration of these data reveals that the studied thrust fault acted as a transverse barrier, dividing the thrust zone into two separate fluid compartments, and a longitudinal drain for migration of fluids. This study also highlights the similarity in deformation processes and mechanisms linked to the evolution of fault zones in compressional and extensional regimes involving carbonate rocks.